Molecular basis of antithrombin deficiency - Luxembourg, Beate; Delev, Daniel; Geisen, Christof; Spannagl, Michael; Krause, Manuela; Miesbach, Wolfgang; Heller, Christine; Bergmann, Frauke; Schmeink, Ursula; Grossmann, Ralf; Lindhoff-Last, Edelgard; Seifried, Erhard; Oldenburg, Johannes; Pavlova, Anna (Thrombosis and Haemostasis, 2011)
Antithrombin (AT) is the most important physiological inhibitor of coagulation proteases. It is activated by glycosaminoglycans such as heparin. Hereditary antithrombin deficiency is a rare disease that is mainly associated with venous thromboembolism. So far, more than 200 different mutations in the antithrombin gene (SERPINC1) have been described. The aim of our study was to characterise the molecular background in a large cohort of patients with AT deficiency. Mutation analysis was performed by direct sequencing of SERPINC1 in 272 AT-deficient patients. Large deletions were identified by multiplex PCR coupled with liquid chromatography or multiplex ligation-dependent probe amplification (MLPA) analysis. To predict the effect of SERPINC1 sequence variations on the pathogenesis of AT deficiency, in silico assessments, multiple sequence alignment, and molecular graphic imaging were performed. The mutation profile consisted of 59% missense, 10% non-sense, 8% splice site mutations, 15% small deletions/insertions/duplications, and 8% large deletions. Altogether 87 different mutations, including 42 novel mutations (22 missense and 20 null mutations), were identified. Of the novel missense mutations, nine are suspected to impair the conformational changes that are needed for AT activation, two to affect the central reactive loop or the heparin binding site, and six to impair the structural integrity of the molecule. Despite the heterogeneous background of AT deficiency, 10 AT variants occurred in multiple index patients. Characterisation of the SERPINC1 mutation profile in large cohorts of patients may help to further elucidate the pathogenesis of AT deficiency and to establish genotype-phenotype associations.
Keywords: Antithrombin deficiency; mutation analysis; DHPLC; thromboembolism